A Comparison of Motivations Behind Tourism Trips to Italy – Travellers of the Grand Tour Era vs. Modern Tourists - Agnieszka Niezgoda (Studia Periegetica, 2019)
The purpose of the article is to compare motivations of travellers visiting Italy in the past, especially in the Grand Tour period, with those of modern tourists. A literature review has revealed that during the Renaissance in the Enlightenment and in the period of the Grand Tour, travel was an opportunity to acquire knowledge, to pursue science and self-development. The empirical part of the article describes results of a study (involving focus group interviews) which indicate that modern tourists also travel to Italy for educational purposes to visit sights that are famous for their historical and artistic qualities. However, for modern tourists such trips are, to a greater extent, opportunities for “an escape from daily life” as well as a chance to get to know the culture, including the local cuisine, new people and a form of rest and recreation. Another important factor, which also played a role in the romantic period, is the desire to boast of the trip on social media.